Energy Embedded Gauss-Seidel Iteration for Soft Body Simulations - Cetinaslan, Ozan; Chaves, Rafael (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.2019.9805, 2019)
In this paper, we present our novel energy embedded Gauss-Seidel iteration to simulate soft objects. Our algorithm is inspired by the equality of the kinetic and potential energy changes, and employs the extended Position-Based Dynamics algorithm (XPBD) as the base algorithm. The proposed method does not aim to conserve the total energy of the system, only alters the position constraints based on the kinetic and potential energy balances within the Gauss-Seidel process of the XPBD algorithm. Our algorithm provides an implicit solution for relatively better visual results during the simulation of soft bodies. Since we apply our solution within the Gauss-Seidel iteration, it is not dependent to both simulation step-size and integration methods. We demonstrate the benefits of our method with many position constraints such as geometric deformation constraints, strain based constraints and continuous materials.